(untitled) (International Journal of Multidisciplinary Perspectives in Higher Education, 2022)
The crown of a successful academic career is often considered an achievement of tenure. The path to tenure may vary based on the type of Carnegie University at which one is employed. Carnegie Doctoral granting R1 Universities place a high priority on conducting research, grant writing and publishing while other Carnegie classified Universities place more emphasis on teaching. Regardless of a University’s Carnegie classification the path to tenure requires sound time management skills if an academic is to achieve tenure. To that end, the authors have decided to revisit Covey’s Time Management Matrix (CTMM). The authors provide an ethnographic perspective with respect to the Quadrants of the CTMM for the purpose of providing a priority driven time self-management instrument to assist academics navigating towards tenure. Priority driven effective time self-management is key to successfully achieving tenure and we forward our academic interpretation of the CTMM as a potential guide for academics and their administrators. Further, the authors suggest that a priority driven effective time self-management strategy is portable across disciplines and national/cultural borders.